Gain characteristics of large volume CuBr laser active media; Optics Communications; Vol. 284, iss. 10-11 - Gubarev F. A. Fedor Aleksandrovich; Troitskiy V. O.; Trigub M. V. Maksim Viktorovich; Sukhanov V. B. Viktor Borisovich (2011, 2011)
Title screen